An evaluation of the Game Changer Password System: A new approach to password security. Issue 100 (April 2017) - M Lennan, Conor T.; Manning, Philip; Tuft, Samantha E.
Abstract: We propose – and experimentally test – a mnemonic variant of password security that uses game positions as passwords. In Experiment 1, we report accuracy and reaction time data when high school student, younger adult, and older adult participants remembered and entered one game-based password, using chess or Monopoly. In Experiment 2, we report accuracy and reaction time data from participants' use of five game-based passwords across 24 sessions over 10 weeks. All five passwords were stored in chess or Monopoly for the initial 20 sessions, and changed (from chess to Monopoly or vice versa) for the remaining sessions. This new approach to password security is both mathematically robust and user-friendly. Highlights: A game-based password security system is proposed and experimentally tested. Participants 14–85 years of age remembered game-based passwords (Exp. 1). Participants 18–50 remembered five game-based passwords over 10 weeks (Exp. 2). Participants chose a variety of pieces and locations to create their passwords. Participants found game-based passwords more fun than traditional passwords.